Sixteen horses - Buchanan, Greg, 1989- (Flatiron Books, 2021)
"A literary thriller from stunning new talent Greg Buchanan, Sixteen Horses is a story of enduring guilt, trauma, and punishment, set in a small seaside community the rest of the world has left behind. In Ilmarsh, England, local police detective Alec Nichols discovers sixteen horses' heads on a farm, each buried with a single eye facing the low winter sun. After Veterinary Forensics expert Cooper Allen travels to the scene, a pathogen is discovered lurking within the soil, and many of those who have come into contact with the corpses grow critically ill. A series of crimes comes to light -- disappearances, arson, and mutilations -- and in the dark days that follow, the town slips into panic and paranoia. Everything is not as it seems. Anyone could be a suspect. And as Cooper finds herself unable to leave town, Alec is stalked by an unseen threat. The two investigators race to uncover the truth behind these frightened and insidious mysteries-no matter the cost"--